Some Stability Charts of A Neural Field Model of Two Neural Populations - í–zgür, Berrak; Demir, Ali (Communications in Mathematics and Applications, 2016)
In this paper, we study on the neural field model of two neuron populations. We make the stability analysis of the linearized model by considering the e¤ect of the synaptic connectivity function. We separate the plane into regions on which we find the number of roots with positive real parts. Hence we find the asymptotic stability region. To separate the plane we use the D-curves and we determine some properties of these curves.